LINGUISTIC FEATURES OF PAREMIOLOGICAL UNITS (Journal of Universal Science Research, 2023)
This article discusses the phraseology, a subject of special linguistics using them in teaching English.  Linguistics as a scientific discipline aims to study the interrelationship and interaction of language and culture. Science is a synthesis of culture and linguistics, and its formation goes back a long time. Science is a synthesis of culture and linguistics, and its formation goes back a long time.